ANALISIS STRATEGI BERSAING PT LIPPO KARAWACI, Tbk DALAM INDUSTRI PROPERTY & REAL ESTATE DI INDONESIA - , Bambang Adikaning Prang ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This study aims to evaluate the strategy of PT. Lippo, Karawaci Tbk in deal with competition on property business in Indonesia, to analyze the strengths, weaknesses, opportunities, and threats of PT. Lippo Karawaci Tbk in deal with competition on property business in Indonesia and analyze Key Success Factor owned by PT. Lippo Karawaci Tbk on property business in Indonesia. The results of SWOT analysis in this study are expected to provide information for PT. Lippo, Karawaci Tbk to adjust the company's resources and capabilities in deal with increasingly fierce of business competition. The performed analysis can also be used as a tool to map the selected strategy of PT. Lippo Karawaci Tbk. Data used in this study is results of data observations and interviews with the management of PT. Lippo, Karawaci Tbk